Effects of ten year old enrichment plantings in a secondary dipterocarp rainforest : a case study of stem and species distribution in Sabah, Malaysia - Luc, Viveca (SLU/Dept. of Forest Ecology and Management, 2010)
Large areas of forests in the tropical region have during the last decades been lost and converted to new land uses while other areas have been degraded into secondary forests. These secondary forests need to be restored and rehabilitation through enrichment planting and liberation may help to speed up the recovery process. The objective of this thesis was to evaluate a rehabilitation method that includes enrichment planting, slashing of weeds and girdling of unwanted trees. The site for the project is situated in Sabah, Borneo in a secondary forest which had been logged and burnt by a wildfire. The project’s goal is to rehabilitate and increase biodiversity through enrichment planting of seedlings mainly belonging to the family Dipterocarpeaceae (dipterocarps). Compositions in terms of families, species, dipterocarps and number of stems were compared between rehabilitated and non- rehabilitated areas using paired plots and ANOVA. On rehabilitated areas enrichment methods of line and gap-cluster planting and maintenance of slashing and girdling of non-dipterocarps were used, whereas the non-rehabilitated areas were not slashed but partly affected by the girdled trees. Ten years after the enrichment planting the double amount of dipterocarp species were found on the rehabilitated area compared to the non-rehabilitated area, which proved to be a significant difference. On the other hand a statistically significant difference with 10 % more families on the non-rehabilitated area was seen. For total number of species, number of stems and dipterocarp stems between the treatments (rehabilitated area and non-rehabilitated area) there were no significant differences. However, in the class sapling a statistically significant difference was found between all families with more stems in the untreated area. In the class saplings of the dipterocarps a tendency was found with more stems in the treated area. This result indicates that planted dipterocarp seedlings have the opportunity, due to the artificial gap, to grow into the next size and become a sapling, whereas in the non-rehabilitated area the forest lacks gaps and seedlings do not have the same prospect to grow. The results suggest that it is possible to increase the number of dipterocarp species using the project’s methods of line and gap-cluster planting with accompanying maintenance. Few projects have been conducted to evaluate active human intervention in the rehabilitation of rainforest. The results described in this study demonstrate the usefulness of enrichment planting. More research of the natural recovery processes of secondary rainforests and continued rehabilitation projects are essential to assist in the development of future rehabilitation strategies. Keywords: artificial gaps, Borneo, Dipterocarpaceae, forest degradation, forest fire, forest rehabilitation, liberation.